Key Stage 3 ELT Coursebook Speech Acts - Liam D. Wilson (Journal of Linguistics and Language Teaching)
The area of pragmatics is an important aspect of the languages that we use in our everyday lives. Speech acts are central to this, and they are often initially presented to language learners in the coursebooks (or textbooks) they read and use during their schooling. This investigation analysed which speech acts were targeted for instruction in junior secondary 3 English language coursebooks used in Hong Kong as learners complete Key Stage 3. The pragmalinguistic and sociopragmatic information presented in these coursebooks was also examined. It was found that certain speech acts (such as advice) were featured far more frequently than others (such as requests). There is also potential for improvement for future coursebooks when it comes to the pragmalinguistic (such as presenting speech acts as part of model dialogues) and sociopragmatic information (such as presenting speech acts being used in situations involving power distance or level of imposition). Therefore, this research contributes valuable findings regarding the speech acts in ELT coursebooks to the field of second language pragmatics.